Effects of jogging and aerobic exercise on body mass index the cardiovascular endurance the strength and endurance leg muscles On undergraduate students Nakhon Ratchasima College - Katngern, Kittikun; Seesensui, Satit (Health Science Journal of Nakhon Ratchasima College, 2023)
Abstract The objectives of this research were to study and compare the effect of jogging and aerobics which affects Body Mass Index, cardiovascular endurance, leg muscle strength and endurance of undergraduate students at Nakhon Ratchasima College. Sample Group were 40 students in regular semester at Nakhon Ratchasima College from years 1 to 4. They divided into 2 groups of 20 people each, obtained by simple random sampling. Samples in experimental group 1 exercised with jogging and experimental group 2 exercised with aerobic dance. The research tools were 1) a jogging exercise program, 2) an aerobic dance exercise program, and 3) The Test Include of a Body Mass Index Test; a 60-second stand test on a Chair, and 3-minutes step up and down test. Statistical analyzed data include Mean (), Standard Deviation (SD), compared means difference between Pre-Training and Post- Training within group and compared values difference of average between groups by Independent T-test. The results showed that 1) Body Mass Index of cardiovascular endurance strength and endurance leg muscle between Pre-test and Post-test within group We found that Experimental Group 1 and Experimental Group 2 were significantly different at the .05 Level. 2) Body Mass Index, cardiovascular endurance strength and endurance leg muscles post-test of those 2 groups were not significantly different.